Sistem Pendukung Keputusan Penilaian Karyawan Terbaik Menggunakan Metode SAW (Studi Kasus: PT. Sango Ceramics Indonesia) - Riko Dwi Jaya; Widiyanto Tri Handoko (INTECOMS: Journal of Information Technology and Computer Science, 2023)
Becoming a company with employees with integrity, and having good skills and quality is the dream of every company. With these employees will later affect the development of a company. PT. Sango Ceramics Indonesia is a large private company engaged in the production of ceramics. The diversity of employees is very complex because the large number of employees makes it difficult for companies to choose the best employees to support the company's development. Therefore, research was conducted to develop a decision support system for selecting the best employees. The SAW method is a method that will later be used in this study, where the calculation process involves the weight value of a criterion which will later be normalized to obtain optimal ranking results. The criteria in this study include 5 assessment contexts, namely discipline, cooperation, communication, activeness, and responsibility. Later this system is expected to help companies recommend which employees are the best and appropriate according to the criteria the company wants.